Certificação internacional de sustentabilidade e carbono: desafios e impactos na promoção da sustentabilidade - Oliveira, Juliana Meneghel de (Universidade Federal de São Carlos, 2025)
This study analyzed the context, challenges, and impacts of implementing the International Sustainability and Carbon Certification (ISCC) in Brazil. Focusing on companies that use waste as raw material for biofuel production, the research adopted a qualitative and exploratory approach to assess the criteria and standards of the certification, as well as its practical applications in the Brazilian context. The growing interest of the European market in Brazilian biofuels was highlighted, as Brazil is one of the world's leading producers of this type of fuel, underscoring the importance of the ISCC in ensuring compliance with international requirements and access to demanding markets such as Europe. The study emphasized the relevance of certification as a tool to promote traceability, environmental compliance, and waste reutilization. However, difficulties in implementation were identified, attributed to the European origin of the standard and the developmental differences between continents. Despite these challenges, the certification has the potential to transform management practices, reduce greenhouse gas emissions, and encourage waste reutilization.
International sustainability ans carbon certification: challenges and impacts in promoting sustainability
Keywords: Carbono; Mudanças climáticas; Certificação; Carbon; Climate changes; Certification; ISCC; ENGENHARIAS; 13. Ação contra a Mudança Global do Clima